Revelation - Osborne, Grant R. (Baker exegetical commentary on the New Testament, 2002)
As with all volumes published in the Baker Exegetical Commentary on the New Testament, Revelation seeks to reach a broad audience with scholarly research from a decidedly evangelical perspective. Each volume in the BECNT series interacts with the best contemporary scholarship, offering up-to-date, accurate, and authoritative analysis of the Greek text through rigorous exegesis and exposition. Central themes are developed throughout, and each exegetical unit is related to the overall message of the biblical book. Pastors and seminarians especially appreciate the combination of broad overview and in-depth analysis found in BECNT volumes, but the series is also popular with scholars and thoughtful lay readers.